Investigating time to first birth among women of reproductive age in Bangladesh: a survival analysis of nationwide cross-sectional survey data - Abdus Sobhan; Mohammed Moinuddin; Md. Moyazzem Hossain (BMC, 2024)
Abstract Background The birth of the first child is an important turning point in a woman's life as it is the starting point of the demanding responsibilities of motherhood and childcare. This study aimed to explore the waiting time and the significant indicators of time to the first birth of aged 15-49 years of ever-married women in Bangladesh. Methods The study considered the most recent country-representative data collected from Bangladesh Demographic and Health Survey (BDHS) in 2017/18. The log-rank test was used to assess the statistical significance of the observed difference between waiting time to first birth and various socio-economic and demographic factors. The Cox proportional hazard model is applied to identify the influential factors for waiting time to first birth. Results About 55% of the respondents' age at their first birth was less than 18 years. More than 21% of them were 20 years and above at their first birth. Findings revealed a higher mean age at first birth in urban areas than in rural areas. Also, in Dhaka and Sylhet region, women have a higher age at first than in other regions of Bangladesh. Results show that the place of residence, region, age at first marriage, age at first sex, respondent's education, employment status, contraceptive use, and mass media exposure were found to be statistically significant determinants of the age of respondents at the time of first birth. Findings also show that a woman from rural areas was likely to be 5% smaller in age at the time of first birth than their counterpart (aHR 1.05; 95% CI 1.01-1.10). The age at first birth of a woman in Chattogram was 24% shorter, while in Rangpur and Barishal, that age was increased by 14% and 8%, respectively. A woman with no education, primary, and secondary education had 28%, 38%, and 29%, respectively, shorter age at first birth than that of the higher educated women. Mass media unexposed women were shorter aged at first birth by 27% (aHR 1.27; 95% CI 1.10-1.47) compared to the women who were mass media exposed. Conclusion It is necessary to increase the age of mothers at first birth which may help to reduce the prevalence of child marriage in Bangladesh. The study findings will be helpful to the policymakers in identifying the gap and designing the programmes targeting the early timing of first birth to reduce child mortality as well as poor maternal outcomes which will be beneficial for achieving the Sustainable Development Goal-3 in Bangladesh.